A Pesca da pescada amarela Cynoscion acoupa (Lacepède, 1801) - Existe relação entre produção, tamanho da embarcação, apetrecho de pesca e pluviosidade? - Lucas Oliveira da, SILVA (2023)
Fishing is an economic and food activity of great importance to humanity, in the Brazilian Amazon coast, which includes the coast of the states of Pará, Amapá and Maranhão, which is considered a highly productive region, and playing an important role for the regional and national economy, the municipality of Bragança is one of the municipalities of the state of Pará with the largest fishing port, In this way, the present work had for purpose to analyze the fishing production of different types of fleets, in result of factors, as days of sea, type of vessel, Catch Per Unit of Effort (CPUE), number of crew and other factors that can be interfering in the final production, and consequently, in the profitability of the activity, altogether seven (7) boats. In this sense, the relation between the fishing gear, which in this case is the gillnet, has its fishing grounds in the salt marsh region, and thus has an inversely proportional relation with the seasonal periods, in the Amazon region, an area where there are large water discharges during the Amazon winter period, This way, it is possible to affirm that the boats that fish yellow hake (Cynoscion acoupa), in the region of the north coast of Brazil, where the seasonal periods are defined in two seasons, dry and rainy, and that they use basically two fishing gears. The espinhel, which has a greater constancy in its production level during the seasonal variables of the year, and gillnet fishery, in turn showed a relationship with the rainfall levels, thus the production peaks are reached in the periods classified as dry, and having low production levels in the periods classified as rainy.